Risk Factors of Sectio Caesarea Delivery at Djafar Harun Hospital - Samsi Burhan; Agusrinal; Ika Sartika; Asmurti (MIRACLE Journal Of Public Health, 2021)
The number of mothers giving birth with sectio caesarae delivery at BLUD R.S H.M Djafar Harun North Kolaka in 2015 was 254 people, then increased in 2016 to 521 people. The purpose of this study was to analyze the risk factors for the incidence of Sectio Caesarea delivery at H.M Djafar Harun Hospital, North Kolaka. This type of research is an analytic observational study with a case-control study approach. The study population was 68 with a sample of 136 people using the Accidental Sampling Technique. Data analysis using the Odds Ratio test. The results of the risk analysis based on narrow pelvic factors showed the value of OR= 9,681; LL= 2,728; UL= 34,355, and then placenta previa factor showed the value of OR= 6,484; LL= 0,759; UL= 55,385. In conclusion, narrow pelvis is a strong risk factor and placenta previa is not a strong risk factor for Sectio Caesarea delivery. It is hoped that the hospital will seek to identify high-risk pregnancies, complications or pregnancy abnormalities so that they can be detected early so that they are able to more optimally handle complications during childbirth.